A SPATIAL ANALYSIS FOR ASSESSING THE SUITABILITY OF ELEMENTARY SCHOOL AS SOCIAL INFRASTRUCTURE AT THE NEIGHBOURHOOD UNIT SCALE IN SUPPORTING CHILD-FRIENDLY SURAKARTA - Rufia Andisetyana Putri; M Dhia Subulussalam; Murtanti Jani Rahayu; Amesta Kartika Ramadhani (Geoplanning: Journal of Geomatics and Planning, 2016)
Problem complexity and interest diversity often cause a city not able to accommodate its population’s needs, among which are the children's needs. It has initiated the idea of the child-friendly city, which got a positive response from the Indonesian government, proven by the policy of child-friendly city/ regency. Surakarta is one of the cities having a strong commitment to being a child-friendly city; however, the implementation has not been comprehensive to the level of neighborhood unit. Elementary school is an essential social infrastructure for children that should be available at a neighborhood unit. However, problems are still there, such as the capacity of elementary schools that is below the national standard and also the children's less safety and comfort in accessing the schools. This paper assesses the suitability of elementary school as a social infrastructure in supporting a child-friendly Surakarta based on four criteria, namely, (a) the serving capacity of the education facility, (b) the safe and comfortable access, (c) the completeness of the elementary schools, and (d) the prevalent access including for disabled children. The suitability measurement was done by using scoring analysis from the results of the field observation as well as the citizens’ and the children's perceptions. The scoring results have shown that most of the elementary schools in Surakarta are still not suitable with the criteria so that they have not been able to support Surakarta as a child-friendly city.